2020
DOI: 10.1200/cci.20.00081
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility and User Perceptions of a Digital System for Electronic Patient-Reported Symptom Monitoring During Routine Cancer Care: Findings From the PRO-TECT Trial

Abstract: PURPOSE There is increasing interest in implementing digital systems for remote monitoring of patients’ symptoms during routine oncology practice. Information is limited about the clinical utility and user perceptions of these systems. METHODS PRO-TECT is a multicenter trial evaluating implementation of electronic patient-reported outcomes (ePROs) among adults with advanced and metastatic cancers receiving treatment at US community oncology practices (ClinicalTrials.gov identifier: NCT03249090 ). Questions der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
143
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(167 citation statements)
references
References 26 publications
4
143
1
Order By: Relevance
“…In one study that administered weekly PRO from the National Cancer Institute’s PRO-CTCAE item library (for symptoms such as pain, nausea, and diarrhea) via mail or telephone and assessed them by using a 5-point ordinal verbal descriptor scale and via PRO questions about physical performance (ECOG) and financial toxicities (The Comprehensive Score for Financial Toxicity [COST-FACIT] questionnaire), it was found that most patients agreed that weekly reporting was a favored frequency for ePRO questionnaire administration in the context of advanced and metastatic cancer treatment [ 22 ]. However, during a more complex or intensive treatment phase, a more frequent (even daily) assessment of more than 8 symptoms might be well regarded and positively associated with an increased use of educational materials about home symptom management.…”
Section: Discussionmentioning
confidence: 99%
“…In one study that administered weekly PRO from the National Cancer Institute’s PRO-CTCAE item library (for symptoms such as pain, nausea, and diarrhea) via mail or telephone and assessed them by using a 5-point ordinal verbal descriptor scale and via PRO questions about physical performance (ECOG) and financial toxicities (The Comprehensive Score for Financial Toxicity [COST-FACIT] questionnaire), it was found that most patients agreed that weekly reporting was a favored frequency for ePRO questionnaire administration in the context of advanced and metastatic cancer treatment [ 22 ]. However, during a more complex or intensive treatment phase, a more frequent (even daily) assessment of more than 8 symptoms might be well regarded and positively associated with an increased use of educational materials about home symptom management.…”
Section: Discussionmentioning
confidence: 99%
“…As early supportive care improves survival in oncology, the solution should contain algorithms to detect symptoms that make a patient eligible for early supportive care [ 3 , 5 , 6 , 18 ].…”
Section: Effectiveness Criteriamentioning
confidence: 99%
“…The solution should allow for follow-up of the patient to detect complications or symptomatic relapse early, which improves clinical utility and patient outcomes [ 3 , 7 ].…”
Section: Effectiveness Criteriamentioning
confidence: 99%
“…Also, in terms of "traditional" outcomes, like measured toxicity, instead of the doctor taking a snap-shot at the outpatient clinic, we believe that toxicity and functioning are better assessed by the patients themselves at multiple time points during follow-up. Fortunately, multiple technological solutions (including established cloud-based solutions, apps, and websites) and tools (such as the validated PRO-CTCAE, EORTC QLQ-C30, and other questionnaires) are readily available (29)(30)(31)(32). As MRgRT study designs are considered, strong consideration should be given to PRO-based endpoints as either primary or complementary objectives.…”
Section: What Endpoints Do We Need To Choose?mentioning
confidence: 99%